Pendekatan Kreatif untuk Menciptakan Peluang Usaha di Dunia Digital - Wolinelo, Juwita; Detumu, Putri Sakina; Mokodompit, Nevalia; Hariana (Politeknik Kebangsaan, 2025)
The digital era drives significant changes in entrepreneurship and creates a need for innovation that aligns with technological developments. This study discusses the importance of creativity and innovation for students in creating new business opportunities, while also examining the development of pin accessories widely used by young people. Conventional pins still use safety pins, which limits their use to fabric-based materials and risks damaging the surface. This condition forms the basis for developing the Magnet Pin Custom, a pin with two installation functions through a combination of a safety pin and a magnet. The study uses a descriptive qualitative method through observation, interviews, and user needs analysis. The results show that the Magnet Pin Custom provides flexible use on various metal surfaces without causing damage, offers customizable designs, and has potential as a creative product with economic value. This project benefits students by enhancing creativity, design skills, and technopreneurship abilities through production processes, digital marketing, and brand development.